Dynamic Functional Molecular Systems: From Supramolecular Structures to Multi‐Component Machinery and to Molecular Cybernetics. Issue 3 (2nd November 2018) - Schmittel, Michael
Abstract: This essay highlights the role of single and multiple reversible self‐sorting events for the development of responsive multi‐component structures as well as multi‐state transformations, devices and machinery. Recent examples illustrate how distinct molecular devices are spatiotemporarily interconnected by chemical signaling to act as integrated machinery and highlight the enormous potential of molecular cybernetics. Abstract :